Engineering properties of geopolymer concrete: a review - Eliana Parcesepe; Carmine Lima; Giuseppe Maddaloni; Maria Rosaria Pecce (Acta Polytechnica CTU Proceedings, 2022)
Geopolymer concrete (GPC) could be a solution that uses a cementless binder and recycled materials for producing concrete, while reducing the carbon dioxide emission and the demand for raw materials. In addition to the environmental aspect, previous studies on GPC showed that it can achieve mechanical characteristics higher than those of ordinary Portland concrete (OPC) such as greater strength a few days after casting, and it can be suitable for structural applications. In this paper, the state-of-the-art review of GPC is presented through an extensive literature analysis to determine the most recent information regarding the engineering properties of geopolymer concrete and the critical issues that prevent its widespread use and to put forward suggestions for future research. In particular, the physical properties in both fresh and hardened states and the mechanical characteristics are investigated; the structural performance of geopolymer concrete elements is also outlined.